Modulation of broiler carcass cholesterol levels through Lactobacillus plantarum intervention - Mursalim; Hafsan; Fatmawati Nur; Faten Khudaer (Talenta Publisher, 2025)
High cholesterol in poultry meat poses a serious public health concern, driving research on healthier animal products. Probiotics such as Lactobacillus plantarum have been investigated for their potential to reduce meat cholesterol through gut microbiota modulation. This study evaluated the effectiveness of L. plantarum derived from Dangke in lowering carcass cholesterol of broiler chickens. The intervention was conducted orally before feeding to ensure precise dosage intake. Four treatment groups were applied: P0 (control), P1 (10⁶ CFU/ml), P2 (10⁸ CFU/ml), and P3 (10¹⁰ CFU/ml). Results showed that P0 had the highest cholesterol level (0.069 mg/dL), while P2 recorded the lowest (0.061 mg/dL), indicating the most significant reduction. This effect is attributed to enhanced colonization of L. plantarum in the cecum, which modulates lipid metabolism and increases bile acid excretion. Beyond cholesterol reduction, broiler performance parameters such as feed conversion ratio (FCR) and body weight gain also improved in probiotic groups, especially at 10⁸ CFU/ml, supporting previous evidence on probiotic efficacy in poultry production. The findings highlight L. plantarum as a promising functional probiotic for reducing cholesterol while enhancing growth efficiency in broilers. From a practical standpoint, incorporation into drinking water may represent a more feasible application strategy, ensuring uniform distribution and easier adoption at the farm level. Future research should address optimal intervention strategies, the sustainability of effects on meat quality, and potential synergistic applications with other probiotics or prebiotics to further enhance poultry health and product safety.